Species of the fuscus and vittatus groups of Pedilus (Coleoptera, Anthicidae: Pedilinae). - Abdullah, Mohammad (Contributions to Entomology = Beiträge zur Entomologie, 1964)
Two groups and eight species of Pedilus from USSR, USA, and Canada are revised in this paper. The fuscus group includes fuscus Fischer, inconspicuus (Horn), flavidus Fall. flabellatus (Horn), and parvicollis Fall. and is distinguished by its longitudinally divided or subapically branched gonostyli or lateral lobes of the male genitalia. The vittatus group includes vittatus (Horn), lineatus Fall. and oregonus Fall., and is distinguished by its internally barbed or toothed gonostyli. Unlike many American species of the genus Pedilus, the elytral apices of males are not modified in the species treated here.